Highly sensitive of an electrochemical DNA biosensor detection towards toxic dinoflagellates Alexandrium minutum (A. minutum) - Zakariah, Emma Izzati; Ariffin, Eda Yuhana; Nokarajoo, Devika; Mohamed Akbar, Muhamad Afiq; Lee, Yook Heng; Hasbullah, Siti Aishah (Elsevier Inc., 2024)
Alexandrium species, including Alexandrium minutum (A. minutum), are capable of producing paralytic shellfish toxins, which frequently adversely affect the aquaculture and fishing industries. Since it's critical, it needs to be precisely detected. This study addresses the development of an electrochemical DNA biosensor for detecting toxic microalga A. minutum gene sequence based on anthraquinone-2-sulfonic acid derivative (AQMS) as the redox DNA hybridisation indicator. DNA binding studies using UV–Vis and molecular docking were performed, confirming the intercalation behaviour. The binding constant (Kb) of such interaction was 4.5 × 105 M−1 with the hyperchromicities shown are 13 and 18 , and the relative binding energies of the docked AQMS towards DNA was − 8.3 kcal mol−1. The RMSD value for AQMS was 0.2 Å, underscoring a remarkably close alignment and similarity with the redocked structure. The aminated DNA probe was then immobilised onto the screen-printed carbon electrode (SPCE) containing polyacrylic microspheres and gold nanoparticles (AuNPs). An excellent linear relationship of the response to DNA concentrations was obtained from 1 × 10−15 M to 1 × 10−5 M (R2 = 0.9908) with a limit detection (LOD) at 6.91 × 10−14 M. This lower detection limit is a significant improvement over several other electrochemical biosensors reported so far for A. minutum determinations. Selectivity experiments demonstrated that this new voltammetric DNA biosensor could distinguish between A. minutum target and non-target DNA and can regenerate after use for up to two cycles. This DNA biosensor has demonstrated its ability to early detect toxic microalgae by effectively differentiating among various non-target dinoflagellate species. Furthermore, the biosensor has been shown to successfully identify A. minutum in water samples from a river in Tumpat, Kelantan, with results comparable to standard polymerase chain reaction (PCR).